Thermal annealing behaviour of Pd Schottky contacts on melt-grown single crystal ZnO studied by IV and CV measurements - Mtangi, W.; Auret, F.D.; Chawanda, Albert; Janse van Rensburg, P.J.; Coelho, S.M.M.; Nel, J.M.; Diale, M.; van Schalkwyk, L. (Elsevier, 2016)
Current–voltage (IV) and capacitance–voltage (CV) measurement techniques have successfully been employed to study the effects of annealing highly rectifying Pd/ZnO Schottky contacts. IV results reveal a decrease in the contact quality with increasing annealing temperature as confirmed by a decrease in the zero bias barrier height and an increase in the reverse current measured at −1.5 V. An average barrier height of (0.77 ± 0.02) eV has been calculated by assuming pure thermionic emission for the as-deposited material and as (0.56 ± 0.03) eV after annealing at 550 ◦C. The reverse current has been measured as (2.10 ± 0.01) × 10−10 A for the as-deposited and increases by 5 orders of magnitude after annealing at 550 ◦C to (1.56 ± 0.01) × 10−5 A. The depletion layer width measured at −2.0 V has shown a strong dependence on thermal annealing as it decreases from 1.09 m after annealing at 200 ◦C to 0.24 m after annealing at 500 ◦C, resulting in the modification of the dopant concentration within the depletion region and hence the current flowing through the interface from pure thermionic emission to thermionic field emission with the donor concentrations increasing from 6.90 × 1015 cm−3 at 200 ◦C to 6.06 × 1016 cm−3 after annealing at 550 ◦C. This increase in the volume concentration has been explained as an effect of a conductive channel that shifts closer to the surface after sample annealing. The series resistance has been observed to decrease with increase in annealing temperature. The Pd contacts have shown high stability up to an annealing temperature of 250 ◦C as revealed by the IV and CV characteristics after which the quality of the contacts deteriorates with increase in annealing temperature.